High-precision laser spectrometer for multiple greenhouse gas analysis in 1 mL air from ice core samples - B. Bereiter; B. Tuzson; P. Scheidegger; A. Kupferschmid; H. Looser; L. Mächler; D. Baggenstos; J. Schmitt; H. Fischer; L. Emmenegger (Atmospheric Measurement Techniques, 2020)
The record of past greenhouse gas composition from ice cores is crucial for our understanding of global climate change. Future ice core projects will aim to extend both the temporal coverage (extending the timescale to 1.5 Myr) and the temporal resolution of existing records. This implies a strongly limited sample availability, increasing demands on analytical accuracy and precision, and the need to reuse air samples extracted from ice cores for multiple gas analyses. To meet these requirements, we designed and developed a new analytical system that combines direct absorption laser spectroscopy in the mid-infrared (mid-IR) with a quantitative sublimation extraction method. Here, we focus on a high-precision dual-laser spectrometer for the simultaneous measurement of CH 4 , N 2 O , and CO 2 concentrations, as well as δ 13 C(CO 2 ) . Flow-through experiments at 5 mbar gas pressure demonstrate an analytical precision (1 σ ) of 0.006 ppm for CO 2 , 0.02 ‰ for δ 13 C(CO 2 ) , 0.4 ppb for CH 4 , and 0.1 ppb for N 2 O , obtained after an integration time of 100 s. Sample–standard repeatabilities (1 σ ) of discrete samples of 1 mL STP (Standard Temperature and Pressure) amount to 0.03 ppm, 2.2 ppb, 1 ppb, and 0.04 ‰ for CO 2 , CH 4 , N 2 O , and δ 13 C(CO 2 ) , respectively. The key elements to achieve this performance are a custom-developed multipass absorption cell, custom-made high-performance data acquisition and laser driving electronics, and a robust calibration approach involving multiple reference gases. The assessment of the spectrometer capabilities in repeated measurement cycles of discrete air samples – mimicking the procedure for external samples such as air samples from ice cores – was found to fully meet our performance criteria for future ice core analysis. Finally, this non-consumptive method allows the reuse of the precious gas samples for further analysis, which creates new opportunities in ice core science.